Feeding tube or Foley catheter for urethral drainage in hypospadias repair: A randomized controlled trial - Vuthiwong, Jaraspong; Mahawong, Phitsanu; Chongruksut, Wilaiwan (Insight Urology, 2019)
Objective: To compare the early complications occurring between indwelling use of a feeding tube and Foley catheter for urethral drainage after hypospadias repair. Material and Method: Sixty boys with proximal or distal hypospadias were included in this prospective study. The patients were randomly divided into 2 groups. In group I a feeding tube was used as a urethral stent and in group II a Foley catheter was used. All patients underwent hypospadias repair by the same surgeon using the bilateral external skin tube (BEST) technique. The patients were followed up at 1-month after surgery for clinical evaluation. Result: There were no statistically significant differences between group I and group II in catheter obstruction, kinking, dislodgment, bladder spasm, hematuria, urinary tract infection, and pain score. At the 1-month follow-up, there were no statistically significant differences between the groups in urethrocutaneous fistula, glans dehiscence, repair breakdown, flap necrosis, hematoma, and wound infection. Five patients in group I (16%) and 1 patient (3%) in group II had catheter dislodgment (p=0.19). Seven patients in group I (23%) and 3 patients (10%) in group II had bladder spasm (p=0.30). Conclusion: The use of a Foley catheter appears to lead to lower bladder spasm and catheter dislodgment rates than the use of a feeding tube. A larger sample size is required for a future randomized controlled study in order to add weight to these findings.